Short-term outcome of patients with elevated serum cardiac troponin I following off-pump coronary artery bypass grafting - Bhattacharjee, Pranab; Ahmed, Istiaq; Hossain Kabir, A. S. M.; Chakrabarty, Tonusree; Gupta, Amit Sen; Sumaia Bin-te Shawkat, M.; Saha, Susmita; Anwar, Mashfiq (International Journal of Research in Medical Sciences, 2024)
Background: Coronary artery disease (CAD) is a global issue at present. It is one of the leading causes of death and disability in men and women in the USA, Western Europe and many other countries. Coronary artery bypass grafting (CABG) is the gold standard for revascularization in coronary artery disease. This study aimed to observe the short-term outcome of patients with elevated serum cardiac troponin I (cTnI) following off-pump coronary artery bypass grafting. Methods: This was a prospective observational study and was carried out at the Department of Cardiac Surgery of the National Heart Foundation Hospital and Research Institute, Dhaka, Bangladesh during the period from July 2020 to October 2021. In this study, we included 80 patients admitted for elective CABG at National Heart Foundation Hospital and Research Institute. Results: Among all patients, 11.3% patients had acute MI, followed by respiratory complication (11.3%), arrythmia (10%), wound infection (6.3%), neurological complication (5%), renal complication (1.3%) and only 2.5% patients died. The mean±SD troponin I in 1st, 2nd and 3rd post operative days of the patients was 10.80±13.39, 7.99±10.39 and 4.73±6.98 respectively. The area under the recipient operational characteristic (ROC) curve was 0.931 with 95% CI were between 0.863 and 0.999, which was statistically highly significant (<0.001). There is no significant association of cTnI with respiratory, renal, neurological complications and wound infection. Conclusions: Our findings showed that there was a significant association between raised cTnI concentrations after OPCAB surgery and adverse events in the early postoperative period.